# Distributive Law Multiplication

Expand the following expression:

(7+3)(a+b)

Use the Distributive Law.

### Comments for Distributive Law Multiplication

 Mar 28, 2011 Distributive Law Multiplication by: Staff The question: What is (7+3)(a+b) answer? The answer: Approach #1: You can add the 7 and the 3 before you apply the distributive law: 7 + 3 = 10 (7+3)(a+b) = (10)(a+b) = 10*a + 10*b = 10a + 10b Approach #2: You can also apply the distributive law this way: (7+3)(a+b) = 7*(a+b) + 3*(a+b) Notice that (a+b) is first multiplied by the 7, and then (a+b) is multiplied by the 3. Finally, the results of the two multiplications are added together. 7*(a+b) = 7*a + 7*b = 7a + 7b 3*(a+b) = 3*a +3*b = 3a +3b = 7a + 7b + 3a + 3b = 7a + 3a + 7b + 3b = 10a + 10b (this is exactly the same answer we got by initially adding the 7 + 3 before applying the distributive law) The final answer is: (7+3)(a+b) = 10a + 10b Thanks for writing. Staff www.solving-math-problems.com

 Sep 29, 2013 distributive this problem by: How about: 9(4x+5y+8)

 Oct 08, 2013 9(4x + 5y + 8) by: Staff 9(4x+5y+8) = (9 * 4x) + (9 * 5y) + (9 * 8) = (9 * 4 * x) + (9 * 5 * y) + (9 * 8) = (36 * x) + (45 * y) + (72) = 36x + 45y + 72 The final answer is: 9(4x+5y+8) = 36x + 45y + 72

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.